2010
DOI: 10.1159/000321574
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Homologies among Vampire Bats Revealed by Chromosome Painting (Phyllostomidae, Chiroptera)

Abstract: Substantial effort has been made to elucidate karyotypic evolution of phyllostomid bats, mostly through comparisons of G-banding patterns. However, due to the limited number of G-bands in respective karyotypes and to the similarity of non-homologous bands, an accurate evolutionary history of chromosome segments remains questionable. This is the case for vampire bats (Desmodontinae). Despite several proposed homologies, banding data have not yet provided a detailed understanding of the chromosomal changes withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…Recent data from chromosome painting, associated with G-banding, confirm that Robertsonian fusions with the complete conservation of chromosome or whole arms, and inversions are the main mechanisms of karyotypic differentiation in the Order Chiroptera [19,20,22,24,25,32]. Herein we found conservatism in many chromosomal segments shared between Micronycteris hirsuta , Phyllostomus hastatus and Carollia brevicauda , but homology of whole chromosomes was not detected in the autosomal set.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…Recent data from chromosome painting, associated with G-banding, confirm that Robertsonian fusions with the complete conservation of chromosome or whole arms, and inversions are the main mechanisms of karyotypic differentiation in the Order Chiroptera [19,20,22,24,25,32]. Herein we found conservatism in many chromosomal segments shared between Micronycteris hirsuta , Phyllostomus hastatus and Carollia brevicauda , but homology of whole chromosomes was not detected in the autosomal set.…”
Section: Discussionsupporting
confidence: 48%
“…These chromosomes have been suggested to be present on the ancestral karyotype of the family Phyllostomidae, since it was present and conserved in the karyotype of such phylogenetically distant species of uncorrelated subfamilies mapping so far [17,18,32]. Although MHI represent a basal clade for Phyllostomidae, and has previously been suggested that basal taxa could contribute to confirm the chromosomal ancestrality [32], we argue that not necessarily basal taxa have primitive karyotypes.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations